Gender differences in adherence to a home-based physical activity program in older adults with memory problems: FABS (Fitness for the Ageing Brain Study) - Cox, K.; Flicker, L.; Almeida, O.; Greenop, K.; Hendriks, Jacqui; Phillips, M.; Lautenschlager, N. (2012)
Background: Higher levels of physical activity (PA) have been associated with better cognitive function. Finding ways to increase PA is an ongoing challenge. Gender differences in adherence to PA interventions are rarely reported and little is known about gender differences in participants with MCI or memory complaints. We aimed to identify gender differences in adherence to a PA program in this target group. Methods: Participants dementia-free but with memory complaints were randomly assigned to a control or PA group. The control group continued their usual PA throughout the study. The PA group were given a home-based program with a target of 150 minutes/week of moderate PA and a behavioural intervention for 6-months. Participants recorded their PA sessions in diaries. Program adherence (PAdh) was calculated from the number of sessions recorded and was defined as the percentage of PA completed compared to the PA prescribed. Total adherence (TAdh) was the number of sessions completed compared to the total number of sessions (baseline sessions + prescribed sessions) expressed as a percentage. Results: The PA group comprised of 51% men (n = 43). At baseline men were significantly older than women 71.1(±SD 8.4) versus 66.0(8.1) years respectively. After 6 months retention was greater for the men (98%) than for women (83%), (P<0.05). Men had higher PAdh than women 79.2 (95% CI, 76.4, 82.1) % versus 65.5 (62.3, 68.6) % (P <0.001). Similarly (TAdh) was 83.6 (81.6, 85.7) % and 72.2 (69.9, 74.5) % (P<0.001) for men and women respectively. Women had significantly greater number of illnesses and injuries 1.2 (0.8, 1.5) than men 0.6 (0.4, 0.9). Further, for TAdh there was a significant interaction between gender and injury with females who reported an injury having 16.31 (5.68, 26.00) % (P< 0.01) higher TAdh than males who sustained an injury. Conclusions: Retention and adherence in this 6 month home-based PA program was greater for men than women. Women experienced more illness and injury than men. This study highlights the need for programs to consider gender differences in the uptake and maintenance of physical activity and plan activities accordingly to improve the effectiveness of interventions.